Holographic Materials and Applications - Kumar, Manoj (IntechOpen, 2019)
Optical techniques continue to evolve and advance, particularly with the inventions of the laser and holography. This volume provides an introduction to various optical systems and devices that are increasingly being used for engineering, scientific, and industrial applications. Organized into three sections on Holographic Materials, Optical Systems, and Algorithms and Imaging Processing, this book covers basic concepts of holographic materials and systems. Chapters provide comprehensive information on volume holograms, display holograms, full-color holographic optical elements, computer-generated holograms, digital imaging devices, and image processing algorithms. This volume is intended for researchers in the field and interested readers alike.